'Needle Crusaders': The Nineteenth-Century Ayrshire Whitework Industry. Issue 1 (May 2016) - Tuckett, Sally
Abstract : Ayrshire whitework, a form of embroidery considered a cheap and popular alternative to lace, was a significant industry in the nineteenth century. Employing thousands of women particularly in the south west of Scotland in the 1850s, the whitework trade combined skill and handicraft with industrial scale organisation, only to decline dramatically by the end of the century. Using census returns, parliamentary reports and contemporary commentary, this article explores the workings of the Ayrshire whitework industry. It will account for the dramatic rise and fall of the industry within the nineteenth century, looking in closer detail at the women of Ayr in particular, and build on existing literature to examine attempts to revive the industry at the turn of the twentieth century.